Land Use and Land Cover Semantics: Principles, Best Practices, and Prospects - Ahlqvist, Ola (CRC Press, 2015)
Explore the Important Role that the Semantics of Land Use and Land Cover Plays within a Broader Environmental Context Focused on the information semantics of land use and land cover (LULC) and providing a platform for reassessing this field, Land Use and Land Cover Semantics: Principles, Best Practices, and Prospects presents a comprehensive overview of fundamental theories and best practices for applying semantics in LULC. Developed by a team of experts bridging relevant areas related to the subject (LULC studies, ontology, semantic uncertainty, information science, and earth observation), this book encourages effective and critical uses of LULC data and considers practical contexts where LULC semantics can play a vital role. The book includes work on conceptual and technological semantic practices, including but not limited to categorization; the definition of criteria for sets and their members; metadata; documentation for data reuse; ontology logic restrictions; reasoning from text sources; and explicit semantic specifications, ontologies, vocabularies, and design patterns. It also includes use cases from applicable semantics in searches, LULC classification, spatial analysis and visualization, issues of Big Data, knowledge　infrastructures and their organization, and integration of bottom-up and top-down approaches to collaboration frameworks and interdisciplinary challenges such as EarthCube. This book: Centers on the link between planning goals, objectives, and policy and land use classification systems Uses examples of maps and databases to draw attention to the problems of semantic integration of land use/cover data Discusses the principles used in a categorization Explores the origins and impacts of semantic variation using the example of land cover Examines how crowd science and human perceptions can be used to improve the quality of land cover datasets, and more Land Use and Land Cover Semantics: Principles, Best Practices, and Prospects offers an up-to-date account of land use/land cover semantics, looks into aspects of semantic data modeling, and discusses current approaches, ongoing developments, and future trends. The book provides guidance to anyone working with land use or land cover data, looking to harmonize categories, repurpose data, or otherwise develop or use LULC datasets.